Invertase inhibition based electrochemical sensor for the detection of heavy metal ions in aqueous system: application of ultra-microlelectrode to enhance sucrose biosensor's sensitivity - Bagal-Kestwal, Dipali; Karve, Meena S.; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Biosensors & Bioelectronics, 2008)
We are reporting fabrication and characterization of electrochemical sucrose biosensor using ultra-microelectrode (UME) for the detection of heavy metal ions (Hg(II), Ag(I), Pb(II) and Cd(II)). The working UME, with 25 mu m diameter, was modified with invertase (INV, EC: 3.2.1.26) and glucose oxidase (GOD, EC: 1.1.3.4) entrapped in agarose-guar gum. The hydrophilic character of the agarose-guar gum composite matrix was checked by water contact angle measurement. The atomic force microscopy (AFM) images of the membranes showed proper confinement of both the enzymes during co-immobilization. The dynamic range for sucrose biosensor was achieved in the range of 1 x 10(-10) to 1 x 10(-7) M with lower detection limit 1 x 10(-10) M at pH 5.5 with 9 cycles of reuse. The spectrophotometric and electrochemical studies showed linear relationship between concentration of heavy metal ions and degree of inhibition of invertase. The toxicity sequence for invertase using both methods was observed as Hg(2+) > Pb(2+) > Ag(+) > Cd(2+). The dynamic linear range for mercury using electrochemical biosensor was observed in the range of 5 x 10(-10) to 12.5 x 10(-10) M for sucrose. The lower detection limit for the fabricated biosensor was found to be 5 x 10(-10) M. The reliability of the electrochemical biosensor was conformed by testing the spike samples and the results were comparable with the conventional photometric DNSA method. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Co-immobilization; Electrochemical biosensor; Heavy metal ions; Invertase (INV)-glucose oxidase (GOD); Mercury; Ultra-microelectrode (UME)